The Role of Management Information Systems in E-Commerce-Based Business Decision Making at Giga Laundry - Andi Indriani Ibrahim; Erna Pujianti; Masni; Suhartini; Nini Andriani; Ayu Putri Utami (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
This study aims to analyze the role of Management Information Systems (SIM) based on the Smartlink application in supporting business decision making in e-commerce-based MSMEs, with a research focus on Giga Laundry. In the digital era that demands accuracy and speed of information, SIM functions not only as a means of recording transactions, but also as a strategic instrument in providing real-time data for operational planning and control. This research uses a descriptive qualitative approach, with data collection through in-depth interviews, direct observation, and documentation studies of Giga Laundry's business activities. The results showed that the implementation of the Smartlink application is able to improve operational efficiency, speed up the service process, and support more accurate and measurable decision making. The app provides financial reports, customer data, and service demand trends that are used as the basis for business evaluation and strategy development. In addition, integration with digital payment systems such as QRIS and bank transfers also strengthens customer trust. This study concludes that SIM plays an important role in encouraging the competitiveness of MSMEs in the digital era and provides recommendations for system development towards a Decision Support System (DSS) in the future.